Field testing two innovative lighting interventions to influence waiting behaviours and movements on stairways in train stations. (May 2022) - Ryan, B; Hallewell, M; Hughes, N; Coad, N; Eliseu, J; Lira, M; Grant, A; Parrott, N; Thompson, K
Features of lighting that can influence people's behaviours have been identified in an earlier study, along with six scenarios where these could be applied to solve problems with movements through railway stations. The current paper describes the development and testing of novel lighting interventions for three of these scenarios, with two new products controlled by the Internet of Things technology integrated with operational railway systems. The first uses projected light to indicate preferred platform waiting locations. The second uses chasing light-emitting diode lighting along a staircase to encourage bi-directional movements. The field study has been carried out in real-world operational railway settings. An evaluation has been based on a theory-based approach to consider whether the lighting functions as intended and whether people react in anticipated ways. The study found that the lighting interventions have been successfully implemented, and there are indications of favourable responses from passengers, though these have been small effects. The approach to evaluation also assists with diagnosis of weaknesses in the initial concepts and determination of the situational factors that can compete with the behaviour influencing effect of the lighting. This enables refinement and further product development. Practical challenges in implementing trials in this type of operational setting have been identified.